The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.jcomdis.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Speech disfluencies of preschool-age children who do and do not stutter

Abstract: Purpose-The goals of the present study were to investigate whether (1) the speech disfluencies of preschool-age children are normally distributed; (2) preschool-age children who do (CWS) and do not stutter (CWNS) differ in terms of non-stuttered disfluencies; (3) age, gender, and speechlanguage ability affect the number and type of disfluencies children produce; and (4) parents' expressed concern that their child stutters is associated with examiners' judgments of stuttered disfluency.Method-Four hundred and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
60
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 60 publications
14
60
0
4
Order By: Relevance
“…Applying a criterion of 3% SLD resulted in high degrees of sensitivity and specificity in young English-speaking children (Ambrose & Yairi, 1999;Pellowski & Conture, 2002;Tumanova et al, 2014), Dutch-Speaking children (Boey et al, 2007), and German-speaking children (Natke et al, 2006). This criterion is also in line with parental concern about their children's stuttering (Tumanova et al, 2014).…”
Section: The Status Of Monosyllabic Word Repetitionmentioning
confidence: 70%
See 1 more Smart Citation
“…Applying a criterion of 3% SLD resulted in high degrees of sensitivity and specificity in young English-speaking children (Ambrose & Yairi, 1999;Pellowski & Conture, 2002;Tumanova et al, 2014), Dutch-Speaking children (Boey et al, 2007), and German-speaking children (Natke et al, 2006). This criterion is also in line with parental concern about their children's stuttering (Tumanova et al, 2014).…”
Section: The Status Of Monosyllabic Word Repetitionmentioning
confidence: 70%
“…Tumanova et al (2014) have shown a very strong discriminatory ability at the threshold of eight disfluencies per 100 words, while Guitar (2013) uses a criterion of no more than 10 disfluencies per 100 words for a normally fluent child. Describing all the disfluencies observed in the speech of young French-speaking children could help improve understanding of the disfluencies to expect in children who do not stutter.…”
Section: The Status Of Monosyllabic Word Repetitionmentioning
confidence: 99%
“…11 GLM was chosen because the present study's speech disfluency data followed a negative binomial distribution (similar to Clark et al, 2013, andLambert, 2014).…”
Section: Data Analysesmentioning
confidence: 99%
“…One of the neurological characteristics of developmental stuttering is the abnormal motor preparation of speech 9 . For proper diagnosis of stuttering, the characterization of disfluencies in speech is fundamental 10 , given that the main manifestation of this disorder is the excessive presence of stuttering-like disfluencies [11][12][13][14] . In addition, knowledge of the stuttering-like disfluency types contributes to define cases of recovered or persistent stuttering in preschool children 15 .…”
Section: Introductionmentioning
confidence: 99%